The encyclopedia of ecology & environmental management (Blackwell Science, 1998)
The Encyclopedia of Ecology and Environmental Management addresses the core definitions and issues in pure and applied ecology. It is neither a short entry dictionary nor a long entry encyclopedia, but lies somewhere in between. The mixture of short entry definitions and long entry essays gives a comprehensive and up-to-date alphabetical guide to over 3000 topics, and allows any subject to be accessed to varying levels of detail; while the longer entries provide general reviews of subjects, the short definitions provide specific details on more specialised areas. An important feature of the Encyclopedia which sets it apart from other similar works is the comprehensive cross-referencing.